Cardiac rehabilitation delivery in low/middle-income countries. Issue 23 (28th June 2019) - Pesah, Ella; Turk-Adawi, Karam; Supervia, Marta; Lopez-Jimenez, Francisco; Britto, Raquel; Ding, Rongjing; Babu, Abraham; Sadeghi, Masoumeh; Sarrafzadegan, Nizal; Cuenza, Lucky; Anchique Santos, Claudia; Heine, Martin; et al.
Abstract : Objective: Cardiac rehabilitation (CR) availability, programme characteristics and barriers are not well-known in low/middle-income countries (LMICs). In this study, they were compared with high-income countries (HICs) and by CR funding source. Methods: A cross-sectional online survey was administered to CR programmes globally. Need for CR was computed using incident ischaemic heart disease (IHD) estimates from the Global Burden of Disease study. General linear mixed models were performed. Results: CR was identified in 55/138 (39.9%) LMICs; 47/55 (85.5% country response rate) countries participated and 335 (53.5% programme response) surveys were initiated. There was one CR spot for every 66 IHD patients in LMICs (vs 3.4 in HICs). CR was most often paid by patients in LMICs (n=212, 65.0%) versus government in HICs (n=444, 60.2%; p<0.001). Over 85% of programmes accepted guideline-indicated patients. Cardiologists (n=266, 89.3%), nurses (n=234, 79.6%; vs 544, 91.7% in HICs, p=0.001) and physiotherapists (n=233, 78.7%) were the most common providers on CR teams (mean=5.8±2.8/programme). Programmes offered 7.3±1.8/10 core components (vs 7.9±1.7 in HICs, p<0.01) over 33.7±30.7 sessions (significantly greater in publicly funded programmes; p<0.001). Publicly funded programmes were more likely to have social workers and psychologists on staff, and to offer tobacco cessation and psychosocial counselling. Conclusion: CR is only available in 40% of LMICs, but where offered is fairly consistent with guidelines. Governments should enact policies to reimburse CR so patients do not pay out-of-pocket.